2018
DOI: 10.1016/j.jad.2018.04.054
|View full text |Cite
|
Sign up to set email alerts
|

A naturalistic examination of the perceived effects of cannabis on negative affect

Abstract: Cannabis reduces perceived symptoms of negative affect in the short-term, but continued use may exacerbate baseline symptoms of depression over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 30 publications
6
69
0
Order By: Relevance
“…Because the dose of cannabinoids and phytochemical makeup of whole-plant cannabis have significant impacts on physiological responses (such as tachycardia) and subjective experiences (such as anxiety), additional research is needed to characterize maximally efficacious treatment protocols. 116 , 157 When used to treat opioid withdrawal symptoms, undesirable side effects also occur in a dose-dependent manner for the FDA-approved cannabinoid dronabinol. 113 The homogenous and consistent formulation of this pharmaceutical combined with the logistical ease of prescribing the drug may make it more feasible than whole-plant cannabis for clinical trials on cannabinoid alleviation of opioid withdrawal symptoms and relapse prevention.…”
Section: Shortcomings Of Cannabis In Medication-assisted Therapymentioning
confidence: 99%
“…Because the dose of cannabinoids and phytochemical makeup of whole-plant cannabis have significant impacts on physiological responses (such as tachycardia) and subjective experiences (such as anxiety), additional research is needed to characterize maximally efficacious treatment protocols. 116 , 157 When used to treat opioid withdrawal symptoms, undesirable side effects also occur in a dose-dependent manner for the FDA-approved cannabinoid dronabinol. 113 The homogenous and consistent formulation of this pharmaceutical combined with the logistical ease of prescribing the drug may make it more feasible than whole-plant cannabis for clinical trials on cannabinoid alleviation of opioid withdrawal symptoms and relapse prevention.…”
Section: Shortcomings Of Cannabis In Medication-assisted Therapymentioning
confidence: 99%
“…In a recent meta-analysis, cannabinoids versus comparator groups had nearly three times the odds of psychiatric or nervous system disorder side effects when studied as a combined endpoint, while individual symptoms (e.g., anxiety, depression) were not statistically significant [44]. In a recent study of medical use, cannabis was shown to reduce neuropsychiatric conditions (i.e., depression, anxiety, and stress) in the short term, while exacerbating depression over long-term use [45]. Nevertheless, FDA labeling recommends screening patients prior to initiating therapy with THC, and this is a recommendation that should be extrapolated to initiation of medical cannabis regimens [25,26].…”
Section: Neuropsychiatric Side Effectsmentioning
confidence: 97%
“…One potential explanation for this increased behavioral efficiency is that CB 1 R agonism attenuates the aversive emotional state associated with impending punishment. Systemic CB 1 R activation in humans has been associated with attenuated anxiety and stress, and produces anti-fear effects (Rabinak et al, 2013;Childs et al, 2017;Cuttler et al, 2018), and complementary data from rodent models demonstrate that CB 1 R agonist treatments have been associated with reduced aversive learning, impaired fear memory acquisition, enhanced fear extinction learning, reduced stress responsivity, and anxiolysis (Kangarlu-Haghighi et al, 2015;Simone et al, 2015;Nasehi et al, 2016;Fokos and Panagis, 2010;Gobira et al, 2013;Kangarlu-Haghighi et al, 2015;Kinden and Zhang, 2015;Schreiber et al, 2018;Uttl et al, 2018). Interestingly, the suppressive effects of cannabinoids on anxiety, fear, and stress appear to stem from CB 1 R activation in the basolateral amygdala (BLA), which is also involved in the integration of information regarding risk of punishment and reward value (Ganon-Elazar and Akirav, 2009;Orsini et al, 2015b;Morena et al, 2016).…”
Section: Direct Cb 1 R Activation Reduces Risky Choice Latencymentioning
confidence: 99%